Sex differences in patients with Non-Small Cell Lung Cancer harboring driver fusions treated with tyrosine kinase inhibitors: a systematic review - Rita Leporati; Édouard Auclin; Daniel Morchón; Miquel Ferriol-Galmés; Juan Carlos Laguna; Teresa Gorria; Cristina Teixidó; Maria Aranzazu Amores; Paolo Ambrosini; Dolores Isla; Giuseppe Lo Russo; Laura Mezquita (Therapeutic Advances in Medical Oncology)
Background: While targeted therapies have transformed the treatment landscape of oncogene-addicted non-small cell lung cancer (NSCLC), the influence of sex on treatment outcomes remains insufficiently understood. Objectives: This systematic review aimed to investigate the impact of sex on clinical outcomes in patients with NSCLC harboring driver fusions treated with targeted therapies enrolled in clinical trials. Data sources and methods: A comprehensive literature search was conducted using PubMed, Embase, and relevant conference abstracts to identify phase III randomized and early clinical trials that reported sex-specific data, including progression-free survival (PFS), overall survival (OS), overall response rate, and adverse events (AEs), in patients with fusion-positive NSCLC treated with tyrosine kinase inhibitors (TKIs). Results: This review involved 10 studies reporting PFS data and 3 studies with OS data, focusing on first-line treatments for ALK fusion (9 studies) and RET fusion-positive (1 study) NSCLC. Pooled analysis of hazard ratios (HRs) for PFS and OS in ALK inhibitors trials revealed no significant differences in survival outcomes based on sex. Additionally, none of the studies provided data on sex-based differences in response rates or toxicities, highlighting a significant knowledge gap regarding the impact of sex on secondary outcomes in targeted therapy. Conclusion: This review found no significant sex-related differences in survival outcomes among patients treated with ALK inhibitors. However, the lack of data on sex-specific response and toxicity emphasizes the need for future research to better understand the role of sex in modulating treatment outcomes and treatment decisions with TKIs.